MODEL PENDANAAN TERORISME MELALUI MEDIA CRYPTOCURRENCY - Prasetya, Adhitya Yuda; Subroto, Athor; Nurish, Amanah (UI Scholars Hub, 2021)
Globalization encourages technological progress so that its development is utilized by terrorist organizations in expanding their movements. Terrorist organizations utilize digital financial transaction technology, namely cryptocurrency, as part of their funding activities. This condition is influenced by the shift in traditional funding methods that have begun to switch to digital media, so the emergence of cryptocurrencies has a great opportunity in terrorism financing activities globally. Over the past few years there has been a phenomenon of using cryptocurrencies by terrorist groups for funding purposes. This research article wants to explain how terrorist organizations use cryptocurrency as a new medium in digital financial funding. The research was conducted using qualitative methods with the theory of the use of funds by terrorist organizations covering the stages of receipt, management, transfer and spending. The results of the study show that cryptocurrencies are at each stage of the use of funds either as a medium or a source of funding which is shown through models or schemes related to the use of cryptocurrencies for terrorism financing. In addition, an exploration of the movement of terrorism financing was carried out from the traditional to the digital realm. Furthermore, recommendations are given regarding the role of the state in efforts to handle the phenomenon of financing terrorism using cryptocurrencies.